The Resolution and Accountability of State Financial Loss In Administrative and Criminal Law Perspectives - Akbar, Muhamad Aksan (Jurnal Hukum Volkgeist, 2023)
Government officials, in performing public legal actions, may abuse their authority, resulting in financial loss to the state, which can have implications for both administrative and criminal resolution and liability. Purposes of this research,  to determine and/or differentiate the resolution of financial loss to the state caused by the abuse of authority by government officials from administrative and criminal law perspectives, in order to avoid criminalizing government officials' actions and weakening the corruption eradication efforts. This research methods, this normative legal research applied a statute approach. The study findings indicate that the abuse of authority causing the state’s financial loss is primarily resolved under administrative law based on Law No. 30 of 2014 concerning Government Administration. This involves the return of the financial loss to the state or regional treasury and the imposition of severe administrative sanctions. However, the abuse of authority causing state financial loss can be treated as a criminal offense if the Internal Supervisory Apparatus (APIP) or law enforcement agencies find elements of a criminal offense as defined in Article 2 paragraph (1) or Article 3 of Law No. 31 of 1999.